Industry 4.0 and the digitalisation of society: Curse or cure? - Tsekeris, Charalambos (Homo Virtualis, 2018)
The central aim of this article is to sketch and outline a brief and critical presentation, overview and assessment of the (radically ambivalent) dynamics of the large family of technological developments pertaining to the Fourth Industrial Revolution (Industry 4.0), as well as of the so-called digitalisation of society. This assessment attempts to comprehensively overcome relevant analytical dualisms and the one-sided “either-or” logic, in favor of a synthetic, open and creative “both-and” framework of interdisciplinary thought.